United States of America. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in the United States during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as health and food safety, sustainability, livestock, cocoa and coffee production, resilience against climate change and reduce the productive gap. Likewise, support was provided for the emergency response caused by the hurricanes in the Caribbean, alliances were created between the public and private sectors, as well as financing. Finally, work was done on the control of chronic kidney disease, on improving agricultural trade and the use of a digital platform "Agrirural", which contains information on historical changes in agricultural and rural life.